Ketahanan Budaya Masyarakat Bali Aga dalam Menciptakan Desa Wisata yang Berkelanjutan - -, Widiastuti (Jurnal Kajian Bali (Journal of Bali Studies); Vol 8 No 1 (2018): MODAL BUDAYA PARIWISATA BALIDO - 10.24843/JKB.2018.v08.i01.p06, 2018)
This article aims to determine the level of cultural resilience in the Bali Aga villages. The level of resilience is measured from the level of morphological changes of the village and the building on site. The study focuses on the development of the village and building morphology on site, resilience level, and factors that shape resilience. The approach used is descriptive qualitative with research locus is in four villages includes Tenganan Pegringsingan Village, Bugbug Village (Regency of Karangasem), Penglipuran Village, and Bayung Gede Village (Regency of Bangli). The result is Tenganan Pegringsingan Village has a very high cultural resilience, Penglipuran Village has high level of cultural resilience, Village Bayung Gede has a low level of cultural resilience, and the lowest level of cultural resilience is Bugbug Village. The most in uential factor on the level of cultural resilience is the internal factors, especially the ability to integrate the traditional management model (social, economic, and culture) and modern management model (tourism). Managing the uniqueness of village assets proves to be an important factor in creating a sustainable tourism village which is shown by the high number of tourist visits continuously.